URBAN PLANNING AND DEVELOPMENT AND THE NEED FOR BALANCING PUBLIC AND PRIVATE INTEREST - Przheska, Tina (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Urban planning and development are processes which can be observed from many different aspects. One of the most essential issues regarding urban planning and development concerns creating a system that provides sustainable urban development. The functionality of such a system is measured primarily by its capacity to provide urban development that is in line with the environmental, social and economic requirements of modern living. Reaching such requirements calls for balancing public and private interests, which more often than not tend to collide. Although there are many contributing factors to the system's functionality, this paper focuses on the regulation concerning urban planning and development and its role in sustainable urban development. The main focus of this paper's research is the regulation of urban planning and development in the Macedonian legal system and its capacity to create a fair balance between public and private interests in the pursuit of sustainable urban development.
Keywords: property law; construction; urban planning; public interest